2020
DOI: 10.3390/molecules25020335
|View full text |Cite
|
Sign up to set email alerts
|

Flame Retardancy of Wood Fiber Materials Using Phosphorus-Modified Wheat Starch

Abstract: Biopolymer-based flame retardants (FR) are a promising approach to ensure adequate protection against fire while minimizing health and environmental risks. Only a few, however, are suitable for industrial purposes because of their poor flame retardancy, complex synthesis pathway, expensive cleaning procedures, and inappropriate application properties. In the present work, wheat starch was modified using a common phosphate/urea reaction system and tested as flame retardant additive for wood fibers. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…All syntheses were carried through in a kneader as described in part 4. Based on former results [14] for synthesis of FR using starch, wheat protein and xylan a molar ratio (AGU:MAP:Urea) of 1:3:4 proved to be optimum. For modification, tannin ratio was 1:1:4.…”
Section: Raw Materials Synthesis and Characterization Of Flame Retardantsmentioning
confidence: 89%
See 3 more Smart Citations
“…All syntheses were carried through in a kneader as described in part 4. Based on former results [14] for synthesis of FR using starch, wheat protein and xylan a molar ratio (AGU:MAP:Urea) of 1:3:4 proved to be optimum. For modification, tannin ratio was 1:1:4.…”
Section: Raw Materials Synthesis and Characterization Of Flame Retardantsmentioning
confidence: 89%
“…It could be confirmed that the flame retardants act exclusively in the condensed phase. The investigations prove that starch-based flame retardants are suitable, representing an alternative to common flame retardants in the wood fiber industry [14]. Thus, further biopolymers were investigated in a similar manner to assess the influence of biopolymer nature.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Based on former investigations using starch or other polysaccharides the modification of HC for application as flame retardant (FR) material was tested. Due to the high amount of reactive hydroxyl groups and the easy accessibility there are good conditions for an effective modification of HC.…”
Section: Hemicellulose Utilizationmentioning
confidence: 99%